Reaffirmation of the Outsider Identity in the Novels U mraku by Ilija Jakovljević and Mladost Tome Ivića by Mate Ujević - Dizdar, Ivana (Anafora, 2024)
This paper explores how the identity of two “outsider” protagonists of selected novels written by Ilija Jakovljević and Mate Ujević is being reaffirmed on the thematic-ideological and expressive level. The analysis will show how well the novels, marked by insufficient and/or delayed reception, fit into Croatian literature of the interwar period and whether they bring any innovations. The hypothesis is that the realist presentation as a technique used by both authors is enhanced by the use of irony as a discursive strategy that can be interpreted in two ways: both as an affirmation of those values advocated by the writers in their programmatic and literary texts and as a negation in the sense of the values’ unsustainability due to the gap with the given hegemonic social values. Such a conclusion is based on explicative and analytical-deductive approaches to the texts as well as on the theoretical assumptions of contemporary researchers of irony and the life and opus of the two writers. The relevance of the topic consists in the (re)examination of the role of interwar literature, whereby the emphasis is placed on insufficiently researched texts and the advocated “soulful” social engagement, which is also (partly) ironized in novels on both individual and collective levels, thus pointing to irony’s potential as a discursive strategy and the importance of the reader as a co-creator of meaning.